The Evolution of Social Media Language: Slang, Emojis, and Linguistic Shifts Across Platforms - SAIMA USMANI, SAIMA USMANI; Musadhique Kottaparamban; Elsadig Hussein Fadlalla Ali; Mohammad Jabir KK (Research Journal in Advanced Humanities, 2025)
This research offers several theoretical and practical developments in the fields of linguistics and communication sciences by offering proof of the presence of social media as a factor of language change. Thus, it also contributes to the development of the existing work by operationalizing and comparing generational discrepancies in the semantic taxonomy of social media terminology, acronymization, and emoticons. The implications of these emerging linguistic practices, as presented in the study, provide useful directions for scholarly analysis, instructional approaches, and professional practice concerning the dynamics of present-day communicational media. In this way, this research fills the gap between the theoretical and the empirical and expands the literature on the way various digital platforms impact language and communication processes